'L' Aquila' Joint Statement on Global Food Security : L' Aguila Food Security Initiative (AFSI) ([s.n.] [S.l.], 2009)
Promotes the development of a global partnership focused on agriculture and food security with the objective of prioritizing the importance of agriculture in the international agenda, launching new investments and improving the efficiency of aid programmes and regional coordination by involving all the partners.
Keywords: FOOD SECURITY